2016
DOI: 10.1111/odi.12465
|View full text |Cite
|
Sign up to set email alerts
|

Altered neural activation pattern during teeth clenching in temporomandibular disorders

Abstract: Decreased activations in cerebral areas associated with motor and cognitive functions in TMDs patients during teeth clenching were observed. Normalized activations of these areas happened in patients after routine treatment. These findings may facilitate the understanding of TMDs pathogenesis and the therapeutic mechanisms of the stabilization splint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…A total of 25 studies published between January 1, 2010 and August 3, 2019 were included (details in Tables 1 and 2 and Additional file 2). Twenty-four MRI studies [22,23,31,32,35,39,[41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] compared patients with TMD and healthy controls, while 1 longitudinal study recruited only patients [60].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 25 studies published between January 1, 2010 and August 3, 2019 were included (details in Tables 1 and 2 and Additional file 2). Twenty-four MRI studies [22,23,31,32,35,39,[41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] compared patients with TMD and healthy controls, while 1 longitudinal study recruited only patients [60].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Four studies [46][47][48][49] used resting-state fMRI (rs-fMRI) to evaluate spontaneous neural function and functional connectivity (FC). Nine studies [50][51][52][53][54][55][56][57]60] used task-state fMRI (ts-fMRI) to investigate regional changes in neural activity during pain perception and modulation, of which 1 study [51] combined resting and task state fMRI and 1 study [50] mixed 3 modalities of ts-fMRI, DTI, and arterial spin labeling (ASL). One study [23] used the single modality of ASL to measure CBF in the whole brain and the brainstem in two steps.…”
Section: Neuroimaging Methods Employed In the Reviewed Studiesmentioning
confidence: 99%
“…The initial search revealed 246 articles and 18 articles that matched the eligibility criteria. The 18 articles consisted of 13 studies on chewing, [26][27][28][29][30][31][32][33][34][35] 7 studies on clenching [36][37][38][39][40][41] and 2 studies on teeth tapping, 42,43 in total 22 studies. The studies on teeth tapping were included in the qualitative meta-analysis analysis only, but not in the ALE meta-analysis, due to the small number of studies in this category.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Many studies on animals have shown that the daily hardness of food affected masseter muscle myosin composition. Furthermore, the type of daily diet also influenced the volume of their masticatory muscle fibers (He et al., ; Maeda et al., ). Additionally, previous reports have shown a reduction and degeneration of muscle fibers in murine masseter muscles subjected to a daily diet of soft foods (Maeda, Suwa, Ichikawa, Masuda, & Kumegawa, ; Maeda et al., ).…”
Section: The Human Masseter Musclementioning
confidence: 99%